Helium conditioning increases cardiac fibroblast migration which effect is not propagated via soluble factors or extracellular vesicles. (10th June 2022) - Kovacshazi, C; Jelemensky, M; Ferenczyova, K; Hofbauerova, M; Kiss, B; Pallinger, E; Kittel, A; Sayour, V N; Gorbe, A; Hambalko, SZ; Kindernay, L; Barancik, M; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Project was supported by the National Research, Development and Innovation Office of Hungary Background: Helium inhalation induces cardioprotection against ischemia/reperfusion injury, of which cellular mechanism is not fully elucidated. Extracellular vesicles (EVs) are cell-derived, nano-sized membrane vesicles which play role in cardioprotective mechanisms, but their function in helium-conditioning (HeC) is not elucidated. Purpose: To investigate, how HeC affects cardiac fibroblasts and if their HeC-induced EVs or other secreted factors mediates remodeling of the cardiac tissue. Methods: Neonatal rat cardiac fibroblasts (NRCF) were exposed to glucose deprivation and HeC rendered by four cycles of 95% helium + 5% CO2 for one hour, followed by one hour of normal culturing conditions. 40 hours later, NRCF migration was analyzed and Western Blot and quantitative PCR were used to analyze the expression of fibroblast to myofibroblast transformation markers. From the cell supernatant, medium-sized extracellular vesicles (mEVs) were isolated with differential centrifugation and analyzed with WB, transmission electron microscopy and nanoparticle tracking analysis. Supernatant of HeC-treated NRCF was transferred to naïve NRCF or immortalized human umbilical vein endothelia cells (HUVEC/TERT2) and migration and in vitro angiogenesis assay was performed. Results: HeC accelerated the migration of NRCF. Meanwhile, HeC did not increase the expression of myofibroblast markers. HeC tended to decrease mEV secretion of NRCFs, but supernatant of HeC-NRCF neither accelerate the migration of naïve NRCF, nor affect the angiogenic potential of HUVEC/TERT2. Conclusion: Since HeC increased the migration of NRCF but HeC-NRCF mEVs did not affect the function of remote cells, HeC may exert its cardioprotective effect via NRCFs, but not affect cardiac remodeling remotely, via NRCF mEVs.